APPLICATION OF THE INDEPENDENT CURRICULUM IN THE DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION LEARNING ACTIVITIES IN MUHAMMADIYAH PRIVATE HIGH SCHOOL 02 MEDAN - Asmila, Winda; Kamil, Kamil (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The Merdeka Curriculuml  isl  anl  educationall  initiativel  thatl  emphasizesl  independencel  inl  learning.l  Thisl  studyl  usedl  qualitativel  descriptivel  method.l  Thel  Merdekal  Curriculuml  makesl  itl  easyl  tol  simplifyl  thel  materiall  froml  beforel  tol  bel  shortl  andl  easierl  andl  adaptedl  tol  thel  needsl  ofl  studentsl  inl  everydayl  life.l  Teachersl  playl  anl  importantl  rolel  inl  thel  teachingl  andl  learningl  processl  ofl  developingl  anl  understandingl  ofl  religiousl  andl  morall  values.l  Inl  addition,l  itl  wasl  foundl  thatl  the application of the Merdeka Curriculum in the subject of Islamic Religious Education provides opportunities for students to be more in-depth in understanding Islam and develop strong moral character. This process also helps students develop better critical thinking skills, creativity, and communication skills. This research provides important insights about the implementation of the Merdeka Curriculum in Islamic Religious Education subjects at SMA Muhammadiyah 02 Medan, and can be an evaluation to develop the application of the Merdeka Curriculum and about how the Merdeka Curriculum can be applied well in Islamic religious education in other schools. The purpose of this study is to find out how the application of the Independent Curriculum in the Development of Islamic Religious Education Learning in Class XI of Muhammadiyah 02 Medan Private High School.